2017
DOI: 10.1007/s40195-017-0556-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al4C3 Particle Size Distribution in a Al–2.5C Master Alloy on the Refining Efficiency of the AZ31 Alloy

Abstract: The Al-2.5C master alloy is prepared to investigate the effect of the Al 4 C 3 particle size distribution on the refining efficiency of the AZ31 alloy. The results indicate that the Al 4 C 3 particles are potent nucleation substrates for primary a-Mg grains. With 1.0 wt% master alloy addition, the grain size is reduced from 204 to 70 lm. The grain refining efficiency of the Al 4 C 3 particles on the AZ31 alloy is calculated to be 0.04%-0.75%. Such low refining efficiency is mainly attributed to the size distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Concerning about the refining mechanism of carbon inoculation of MgAl alloys, two kinds of AlC-rich compounds Al 4 C 3 and Al 2 MgC 2 were considered to be the potent nuclei for Mg grains due to the low disregistry with ¡-Mg phase. 22) It is worth noting that AlCO particles were invariably observed in the carbon-inoculated MgAl based alloys, 42) as the particle A shown in Fig. 7.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Concerning about the refining mechanism of carbon inoculation of MgAl alloys, two kinds of AlC-rich compounds Al 4 C 3 and Al 2 MgC 2 were considered to be the potent nuclei for Mg grains due to the low disregistry with ¡-Mg phase. 22) It is worth noting that AlCO particles were invariably observed in the carbon-inoculated MgAl based alloys, 42) as the particle A shown in Fig. 7.…”
Section: Discussionmentioning
confidence: 82%
“…In practice, it is found that the nucleated particles which play the role of heterogeneous nucleation are often less than 1% of the total nucleation particles. 42) According to the free growth model:…”
Section: Discussionmentioning
confidence: 99%
“…For the past decade, grain refinement has become one of the most important routes to improve the mechanical properties of magnesium alloys [1,2,3]. The main grain refining methods for Al-bearing Mg alloys includes superheating [4], Elfinal processing [5], carbon inoculation [6,7,8], and solute addition [9,10,11,12,13]. Among these techniques, carbon inoculation is attracting widespread interest due to its low cost, low operating temperature, and less fading.…”
Section: Introductionmentioning
confidence: 99%